Application of Agile Marketing Vocational Higher Education at the Politeknik Negeri Pariwisata Makassar - Eljihad Akbari Syukriah M; Jenica Sampe Pande; Najmi Kamariah (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2023)
This research was conducted to provide empirical and theoretical concepts to characterize the capabilities of agile marketing in vocational higher education in effective marketing for organizations in developing higher education institutions that are run. The research was conducted at the Makassar Tourism State Polytechnic, South Sulawesi. The research method used is descriptive qualitative, interviews and literature studies. The implementation of agile marketing higher education organizations must learn from the inputs and results obtained when the marketing strategy is carried out in collaboration with work teams. Organizations need to use data to make smarter decisions, but we also need to be aware of how bias in interpretation can mislead the vocational education organization. Ensuring that teams can best learn through a process, correct course when needed and validate their learning while the strategy is being implemented. The results of this study provide an overview of adaptability to changing conditions, Collaborative and integrated Working Environment, Continual and fast pace Innovation and Forecasting and monitoring of market needs can be an operating model used to redefine the process, structure and mindset of how the marketing team works so that delivery strategies can be more adaptive and responsive and more customer focused and result in effective marketing. This study recommends establishing an organizational model that has marketing goals and is centered on consumer needs.